Morphological-aesthetic criteria: Design of floats in the Festival of Fruits and Flowers in Ecuador (Ágora de Heterodoxias, 2019)
The Festival of Fruits and Flowers (FFF), that takes place every year in Ambato (Ecuador), serves as a platform for the staging of a set of allegorical cars that mean and represent at all times the best of a city thriving that tries to communicate, through their communities of artists, their desires, joys, their identities and particular conceptions of world and nature. Based on this reality, the general objective of this article lies in analyze the morphological-aesthetic criteria present in the design of floats of the referred festival. Methodologically, this research combines semiotic analysis with an aesthetic reflection within the framework of design. It is concluded that the forms about the artistic representation that gives life to the floats in the FFF, with which and from which, a multivariate set of aesthetic and morphological criteria are developed that identify, at the same time, the artist or group of artists and their work, not only give an account of the artistic representations that ambateños share about their ways of life; but, also, their practices, rituals, symbols and signs that serve to build the festive space as a precisely space of creation and intersubjective meeting.
Keywords: morphological-aesthetic criteria; floats; Feast of Fruits and Flowers; Ambato; semiotic analysis